A web-based tool to design and analyze single- and double-stage acceptance sampling plans. Issue Volume 32:Issues 1(2020) (2nd January 2020) - Luca, Stijn; Vandercappellen, Johan; Claes, Johan
Abstract: Acceptance sampling plans are used to determine whether production lots can be accepted or rejected. Existing tools only provide a limited functionality for the two-point design and the risk analysis of such plans. In this article, a web-based tool is presented to study single- and double-stage sampling plans. In contrast to existing solutions, the tool is an interactive applet that is freely available. Analytic properties are derived to support the development of search strategies for the design of double-stage sampling plans that are more efficient and accurate in comparison with existing routines. Several case studies are presented.